EMOTIONAL INTELLIGENCE IN LEADERSHIP: ITS INFLUENCE ON EMPLOYEE RETENTION IN THE DIGITAL ERA - Rika Solihah; Amalia Juliana Monika Intan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Employee retention is a critical challenge for organizations, particularly in the digital era marked by rapid technological advancements and dynamic workplace environments. This study examines the influence of emotional intelligence in leadership, focusing on empathy and stress management, on employee retention, with job satisfaction serving as an intervening variable. Using a quantitative research design, data were collected from 50 employees of Halodoc in Bandung through a total sampling technique. The analysis, conducted using Structural Equation Modeling (SEM) with SmartPLS, revealed that empathy and stress management have significant direct effects on job satisfaction and employee retention. Moreover, job satisfaction was found to play a pivotal mediating role, amplifying the indirect effects of empathy and stress management on retention outcomes. These findings highlight the importance of fostering emotionally intelligent leadership to enhance job satisfaction and reduce turnover rates. The study contributes to the theoretical understanding of emotional intelligence in leadership while offering practical insights for organizations to strengthen their retention strategies in the digital era. Future research is encouraged to explore these relationships in remote and hybrid work contexts.